PEMBELAJARAN MENULIS PUISI BERORIENTASI MAJAS DENGAN MENGGUNAKAN METODE CREATIVE LEARNING PADA SISWA KELAS X SMA AL-HIDAYAH CIPARAY KABUPATEN BANDUNG - Nugraha, Eggie; Priatna, Asep (STKIP Subang, 2017)
Today the development of Indonesian literature is growing rapidly. One effort to encourage the advancement of Indonesian literature is to improve the teaching of literary appreciation at every level of school. In order for students interested in learning to write poetry so as to develop creations and imagination. Based on the above background, the author is interested in conducting research on